2022
DOI: 10.1093/ehjci/jeac222
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac computed tomography following Watchman FLX implantation: device-related thrombus or device healing?

Abstract: Aims Cardiac computed tomography (CT) is increasingly utilized during follow-up after left atrial appendage closure (LAAC). Hypoattenuated thickening (HAT) is a common finding and might represent either benign device healing or device-related thrombosis (DRT). The appearance and characteristics of HAT associated with the Watchman FLX have not been previously described. Therefore, we sought to investigate cardiac CT findings during follow-up after Watchman FLX implantation with a focus on HAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…TAVR and MitraClip [Abbott]), those with specific indications (e.g., very low or very high risk for bleeding or stroke or cerebral amyloid angiopathy), those that optimise procedural strategies (e.g., ICE or composite angio/ CT-fused imaging), and new technologies such as coated surfaces. (Reproduced with permission from 99 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TAVR and MitraClip [Abbott]), those with specific indications (e.g., very low or very high risk for bleeding or stroke or cerebral amyloid angiopathy), those that optimise procedural strategies (e.g., ICE or composite angio/ CT-fused imaging), and new technologies such as coated surfaces. (Reproduced with permission from 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using TOE, DRT is defined as a homogeneous, echo-dense mass adherent to the atrial surface of the LAAO device visible in multiple projections 36 . Cardiac CT relies on the detection of subtle changes of HAT on the atrial surface which may not be readily detected by TOE 36,99 (Figure 21). Categorisation of HAT into low or high grade is based on imaging characteristics of the HAT localisation, extent and morphology which may help guide clinical management based on the assumption that subtle changes likely represent device healing and carry a low embolic risk 36 .…”
Section: Drtmentioning
confidence: 99%
See 1 more Smart Citation
“…hypoattenuated thickening), jo dažnį bei fenotipus po KPrA uždarymo procedūros "Watchman FLX" uždarikliu, siekiant nustatyti KPrAU trombozę. Nors tyrimo metu nebuvo vertinta koreliacija tarp skirtingų KT radinių ir kli-nikinių įvykių, tačiau yra pagrindas tolesniems tyrimams, nes tai buvo pirmasis tyrimas, vertinantis normalų gijimo procesą ir įvairius fenotipus stebint kontrastinės medžiagos ryškumo sumažėjimą sustorėjimo zonose arba kitaip KPrAU trombozę [12].…”
Section: Tyrimo Rezultataiunclassified
“…Long-term follow-up studies have indicated that LAAC intervention can mitigate the thrombotic risk associated with LAA thrombus formation, concurrently minimizing the bleeding risks associated with anticoagulant use [ 4 , 5 ]. Notably, device-related thrombosis (DRT) after successful closure implantation on LAA poses a major challenge, with reported incidence ranging from 3% to 5%, associated with an increased risk of thrombus events [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%